Study on Adjustment Problems of Elderly living in Old Age Home and Within Family set up in Gwalior City - Kushwah, Archana; Bhadauria, Shailendra Singh (Indian Journal of Extension Education, 2021)
The number of older person rising in the 21st century in the country consequently, there are certain problems in different region and cultures. Adjustment is a common problem in old age and it is difficult to adjust due to limited capacity, lower mental ability and increased dependency on others. The present investigation is an attempt to study adjustment problems of old age, residing in old age home and with their families. Purposive random sampling technique was used to select 100 elderly persons aged between 60 to 70 years (50 each from the old age home and family setups) of Gwalior, Madhya Pradesh. Shamsad-jasbir Old-age Inventory (SJOAI, 1995) was used to measure the variables. The findings of the study showed higher adjustment problems in old age living in old age home, than in family setups.